Degradation of tetracyclines by peracetic acid and UV/peracetic acid: Reactive species and theoretical computations. (April 2023) - Meng, Liang; Dong, Jiayue; Chen, Jing; Lu, Junhe; Ji, Yuefei
Abstract: As an environment-friendly oxidant and disinfectant, peracetic acid (PAA) and PAA based-advanced oxidation processes (AOPs) for the treatment of emerging micropollutants have raised increasing interest, owing to their ease of activation and less generation of harmful disinfection byproducts. Tetracyclines (TCs) antibiotics as a group of wide-spectrum antibiotics are frequently detected in sewage effluents, while the knowledge of PAA-based advanced oxidation reactions to remove the substrates is quite limited. In this work, we systematically investigated the kinetics and underlying transformation mechanisms of three TCs including tetracycline (TTC), oxytetracycline (OTC), and chlortetracycline (CTC) in the UV-activated PAA oxidation process. The results indicated that three TCs can be efficiently decayed by UV/PAA. The pseudo-first-order reaction rate constants ( k obs ) of TCs followed the order: k CTC (0.453 min −1 ) ≫ k TTC (0.164 min −1 ) >  k OTC (0.158 min −1 ). Quenching experiments showed that the removal of CTC was mainly ascribed to the direct oxidation of PAA, while TTC and OTC were more susceptible to free radicals. The k obs values of the three TCs by PAA oxidation presented a fairly well correlation to the global nucleophilicity and the activation energies of the TC molecules, highlighting the structure-specific reactions of TCs to PAA. Based on product identification and theoretical calculation, N-demethylation and hydroxylation were proposed as the main pathways for TCs degradation by PAA non-radical oxidation. The combination of PAA and UV irradiation can further improve the degradation efficiency of TCs and contribute to reducing the diffusion and transmission of resistance genes in the environment. Graphical abstract: Image 1 Highlights: Degradation of TCs by UV/PAA followed the order of CTC > TTC > OTC. PAA shows higher reactivity toward CTC than the other two TCs. Reactivities of TCs toward PAA are related to the global nucleophilicity. PAA reacts with TCs preferentially via N-dealkylation.